2015
DOI: 10.1371/journal.pone.0138078
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Cholesterol-Lowering Probiotics and Anthraquinone from Cassia obtusifolia L. Ameliorate Non-Alcoholic Fatty Liver

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become a common liver disease in recent decades. No effective treatment is currently available. Probiotics and natural functional food may be promising therapeutic approaches to this disease. The present study aims to investigate the efficiency of the anthraquinone from Cassia obtusifolia L. (AC) together with cholesterol-lowering probiotics (P) to improve high-fat diet (HFD)-induced NAFLD in rat models and elucidate the underlying mechanism. Cholesterol-lowering p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 50 publications
2
52
0
2
Order By: Relevance
“…Likewise, the gut microbiota composition could also contribute to the development of NAFLD independently of obesity [29]. It has been previously reported that feeding a high fat diet caused gut microbiota imbalance as a mechanism involved in obese-related NAFLD development, justifying the adequacy of the current study [38,39]. As expected, in our murine model of NAFLD metagenomic studies revealed differences at phylum, class and genus levels between HFD-fed mice and controls, leading to dysbiosis.…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, the gut microbiota composition could also contribute to the development of NAFLD independently of obesity [29]. It has been previously reported that feeding a high fat diet caused gut microbiota imbalance as a mechanism involved in obese-related NAFLD development, justifying the adequacy of the current study [38,39]. As expected, in our murine model of NAFLD metagenomic studies revealed differences at phylum, class and genus levels between HFD-fed mice and controls, leading to dysbiosis.…”
Section: Discussionsupporting
confidence: 62%
“…A few studies have indicated possible roles of the gut microbiota in influencing host energy metabolism through PPAR-a (204)(205)(206)(207)(208). It is now known that the gut microbiota responds to nutrient deprivation by augmenting the PPAR-a-dependent fatty acid oxidation and the hepatic production of ketone bodies via the PPAR-a-dependent ketogenesis pathway (205,209).…”
Section: Ppar Microbiota and The Livermentioning
confidence: 99%
“…Adipose tissue releases cytokines to increase inflammation and fibrosis. Gut microbiota is also believed to play a role in the development of NASH via alterations in the BA pool level and composition (Jiang et al, 2015; Liu et al, 2016b; Mei et al, 2015; Wang et al, 2016). Recently, vitamin D deficiency has been proposed as another possible factor as mice fed a high fat diet (HFD) exhibited increased steatosis and hepatic ballooning when coupled with a vitamin D deficiency (Kong et al, 2014).…”
Section: Nafld and Nashmentioning
confidence: 99%